PERALIHAN MATA PENCAHARIAN MASYARAKAT SAROLANGUN: DARI PETANI KARET KE PENAMBANG EMAS LIVELIHOOD TRANSITION OF THE SAROLANGUN COMMUNITY: FROM RUBBER FARMERS TO GOLD MINERS - Irhas Fansuri Mursal; M. Ali Munazir; Gusmira Wita; Ulul Azmi (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2026)
Structural transformations in rural economies are often driven by commodity price dynamics and external pressures on primary livelihoods. This article examines the livelihood transition of the Sarolangun community, Jambi Province, from smallholder rubber plantations to artisanal gold mining as a response to economic instability and shifts in the socio-environmental landscape. The study aims to explain the initial emergence of smallholder rubber cultivation, analyze its development leading up to the 1997 economic crisis, and identify the processes and driving factors behind the shift toward gold mining activities. Employing a narrative literature review approach and phenomenology, this article synthesizes findings from recent scholarly works to depict the characteristics of rubber production systems, structural challenges within the agrarian sector, and the socioeconomic drivers of the transition to extractive livelihoods. The results reveal that declining productivity, global price fluctuations, and weak market institutions compelled communities to adopt more liquid and immediate income strategies, notably traditional gold mining. This transition has significantly altered social relations, household economic structures, and the local ecological balance.